Surgical site infection prevention practice and associated factors among nurses working at public hospitals of the western part of southern nation, nationalities, and peoples’ region, Ethiopia: A cross-sectional study - Tesfaye, Tamene; Dheresa, Merga; Worku, Teshager; Dechasa, Deribe Bekele; Asfaw, Henock; Bune, Abera Jambo (Frontiers in Surgery, 2022)
Background Surgical site infection is a major hazard for surgical patients and compromises their quality of life. Its effect is higher in developing countries compared to developed countries. Most of the studies done in Ethiopia regarding surgical site infection prevention practice on nurses who were not directly exposed to wound care, thus it produces less reliable results. Therefore, we aimed to assess surgical wound infection prevention practice among nurses who are directly involved in the care. Objective To assess surgical site infection prevention practice and associated factors among nurses working at public hospitals in the western part of the southern nation, nationalities, and peoples’ regions from March 1–31, 2020. Methods An institutional-based cross-sectional study design was conducted from March 1–31, 2020 among randomly selected 402 study participants. A structured and pretested questionnaire was used. EpiData Version 3.1 and Statistical Package for Social Science Version 20 were used for analysis. Bivariable and multivariable analysis was undertaken and p-value less than 0.05 at a 95% confidence interval was considered statistically significant. Results The overall good self-reported surgical site infection prevention practice of nurses was 46% (95% CI: 41.3, 50.7). Nurses who were BSc degree (AOR = 2.04; 95% CI: 1.31, 3.18), working in the units having surgical site infection prevention guidelines (AOR = 2.45; 95% CI: 1.34, 4.47), had ever taken infection prevention training (AOR = 2.23; 95% CI: 1.42, 3.49), had good knowledge (AOR = 1.82;95% CI: 1.13, 2.90) and had good attitude (AOR = 2.61;95% CI: 1.67, 4.10) performed good surgical site infection prevention activities as compared to their counterparts. Conclusion Nurses’ surgical site infection prevention practice was found to be low. To upgrade nurses’ practice the hospitals should develop their surgical site infection prevention guidelines based on WHO recommendations and provide training on it.